Differential effects of risuteganib and bevacizumab on AMD cybrid cells. (February 2021) - Schneider, Kevin; Chwa, Marilyn; Atilano, Shari R.; Shao, Zixuan; Park, John; Karageozian, Hampar; Karageozian, Vicken; Kenney, M. Cristina
Abstract: Purpose: Intravitreal injections of anti-vascular endothelial growth factor (VEGF) treatments are currently used to treat wet age-related macular degeneration (AMD), diabetic retinopathy, and macular edema. Chronic, repetitive treatments with anti-VEGF may have unintended consequences beyond the inhibition of angiogenesis. Most recently, clinical trials have been conducted with risuteganib (RSG, Luminate®), which is anti-angiogenic and has neuroprotective and anti-inflammatory properties. Mitochondrial damage and dysfunction play a major role in development of AMD. Transmitochondrial cybrids are cell lines established by fusing human retinal pigment epithelial (RPE) cells that are Rho0 (lacking mtDNA) with platelets isolated from AMD subjects or age-matched normal subjects. Cybrid cell lines have identical nuclei but mitochondria from different subjects, enabling investigation of the functional consequences of damaged AMD mitochondria. The present study compares the responses of AMD cybrids treated with bevacizumab (Bmab, Avastin®) versus risuteganib (RSG, Luminate®). Methods: Cybrids were created by fusing mtDNA depleted ARPE-19 cells with platelets from AMD or age-matched normal patients. AMD (n = 5) and normal (n = 3) cybrids were treated for 48 h with or without 1x clinical dose of 1.25 mg/50 μl (25, 000 μg/ml) of Bmab or 1.0 mg/50 μl (20, 000 μg/ml) of RSG. Cultures were analyzed for levels of cleaved caspase 3/7 and NucLight Rapid Red staining (IncuCyte® Live Cell Imager), mitochondrial membrane potential (ΔΨm, JC1 assay) or reactive oxygen species (ROS, H2DCFDA assay). Expression levels of genes related to the following pathways were analyzed with qRT-PCR: Apoptosis ( BAX, BCL2L13, CASP-3, -7, -9 ); angiogenesis ( VEGFA, HIF1α, PDGF ); integrins ( ITGB-1, -3, -5, ITGA-3, -5, -V ); mitochondrial biogenesis ( PGC1α, POLG ); oxidative stress ( SOD2, GPX3, NOX4 ); inflammation ( IL-6, -18, -1β, IFN-β1 ); and signaling ( P3KCA, PI3KR1 ). Statistical analyses were performed using GraphPad Prism software. Results: The untreated AMD cybrids had significantly higher levels of cleaved caspase 3/7 compared to the untreated normal cybrids. The Bmab-treated AMD cybrids showed elevated levels of cleaved caspase 3/7 compared to untreated AMD or RSG-treated AMD cybrids. The Bmab-treated cybrids had lower ΔΨm compared to untreated AMD or RSG-treated AMD cybrids. The ROS levels were not changed with Bmab or RSG treatment. Results showed that Bmab-treated cybrids had higher expression levels of inflammatory ( IL-6, IL1-β ), oxidative stress ( NOX4 ) and angiogenesis ( VEGFA ) genes compared to untreated AMD, while RSG-treated cybrids had lower expression levels of apoptosis ( BAX ), angiogenesis ( VEGFA ) and integrin ( ITGB1 ) genes. Conclusions: These data suggest that the mechanism(s) of action of RSG, an integrin regulator, and Bmab, a recombinant monoclonal antibody, affect the AMD RPE cybrid cells differently, with the former having more anti-apoptosis properties, which may be desirable in treating degenerative ocular diseases. Highlights: Human AMD cybrids were treated with either risuteganib (RSG, Luminate®) or with bevacizumab (Bmab, Avastin®). Cultures were evaluated for levels of cell viability, reactive oxygen species and expression of genes of the inflammation, oxidative stress and angiogenesis pathways. Bmab-treated AMD cybrids showed increased apoptosis and lower mitochondrial membrane potential compared to untreated and RSG-treated cultures. Elevated expression levels of inflammatory, oxidative stress and angiogenesis genes were found in the Bmab-treated cybrid cells. In conclusion, RSG elicits less cytotoxicity in AMD cybrid cells than Bmab treatment.